2020
DOI: 10.1596/1813-9450-9241
|View full text |Cite
|
Sign up to set email alerts
|

Jobs' Amenability to Working from Home: Evidence from Skills Surveys for 53 Countries

Abstract: The spread of COVID-19 and implementation of "social distancing" policies around the world have raised the question of how many jobs can be done at home. This paper uses skills surveys from 53 countries at varying levels of economic development to estimate jobs' amenability to working from home. The paper considers jobs' characteristics and uses internet access at home as an important determinant of working from home. The findings indicate that the amenability of jobs to working from home increases with the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 3 publications
5
99
0
9
Order By: Relevance
“…The findings in Fig. 3 are consistent with the argument of Hatayama et al ( 2020 ) that women tend to have jobs that are more amenable to working from home than the average worker. However, within the same gender, there is remarkable difference in the work-from-home behavior according to whether citizens have children in primary school, although having children in junior high school did not make difference.…”
Section: Design Of Surveys and Datasupporting
confidence: 89%
See 1 more Smart Citation
“…The findings in Fig. 3 are consistent with the argument of Hatayama et al ( 2020 ) that women tend to have jobs that are more amenable to working from home than the average worker. However, within the same gender, there is remarkable difference in the work-from-home behavior according to whether citizens have children in primary school, although having children in junior high school did not make difference.…”
Section: Design Of Surveys and Datasupporting
confidence: 89%
“…Part-time workers are more likely to lose their jobs than full-time workers, especially in emergency situations. Salaried and formal workers have jobs that are more amenable to working from home than the average workers (Hatayama et al 2020 ). To scrutinize the effect of having children who attend school, it is important to compare people that have similar jobs.…”
Section: Design Of Surveys and Datamentioning
confidence: 99%
“…In less developed countries workers have fewer opportunities to work from home due to technological limitations as well as the industrial composition. For example, amenability of homeworking is decreased with the level of development since agricultural and other low productivity jobs are not possible to perform from home (Gottlieb et al, 2020;Hatayama et al, 2020). Hence, developing economies differ significantly from the advanced countries both in terms of the availability of occupations that can be teleworked and number of people employed in such jobs.…”
Section: Brief Review Of Covid-19 and Labor Marketsmentioning
confidence: 99%
“…Hence, developing economies differ significantly from the advanced countries both in terms of the availability of occupations that can be teleworked and number of people employed in such jobs. Nevertheless, it has also been found that highly educated, well-paid and less vulnerable workers are typically concentrated in teleworkable jobs in developing and developed world (Delaporte and Rena, 2020;Hatayama et al, 2020).…”
Section: Brief Review Of Covid-19 and Labor Marketsmentioning
confidence: 99%
See 1 more Smart Citation